BUDIDAYA TANAMAN TOMAT DENGAN IRIGASI TETES UNTUK MENINGKATKAN PENDAPATAN MASYARAKAT PESISIR - Rizka Wildani 1) Mulyadi1) Muhammad Nazarul Yanis 1) Puja Triandini1) Anzana Putra 1) Tri Rahayu2) (Jurnal Pengabdian Kepada Masyarakat Agri Hatantiring, 2024)
Tomatoes are fruits and vegetables that are widely consumed by the community in various types of processed and fresh. The purpose of this service is to guide the Pantai Harapan Village Community to be able to cultivate tomatoes based on water-saving technology with drip irrigation sustainably to increase income. The methods used are technical assistance and learning by doing. With the technical guidance on tomato cultivation through drip irrigation, the community's knowledge and skills have gradually increased. This is supported by the evaluation results which show an increase in knowledge and production. Keywords : tomatoes, income of coastal communities, cultivation, drip irrigation